The Most Highly Cited Publications on Basketball Originate From English-Speaking Countries, Are Published After 2000, Are Focused on Medicine-Related Topics, and Are Level III Evidence - Zachary D. Griffin, B.S; Jordan R. Pollock, B.S; M. Lane Moore, B.S; Kade S. McQuivey, M.D; Jaymeson R. Arthur, M.D; Anikar Chhabra, M.D (Elsevier, 2022)
Purpose: To identify the 50 most highly cited research publications in the sport of basketball. Methods: Using the Clarivate Analytics Web of Knowledge database and the search term "basketball", we identified 2,704 articles. These articles were filtered by the total number of citations and the top 50 most cited articles with a central focus on basketball were selected for this analysis. For each article, we further identified and analyzed author name, publication year, country of origin, journal name, article type, main research topic area, competitive level, gender of study population, and the level of evidence. Results: Medicine-related topics, particularly those involving knee injuries, are more common than nonmedical topics (coaching, sports psychology etc.) among the highest cited articles. Articles originated from 13 different countries, with 48% originating in the United States. Only four authors had more than one article included in the top 50 most cited articles. Conclusion: A majority of the top 50 research articles were from English-speaking countries, published after 2000, primarily focused on medicine-related topics, and were Level III evidence. Publications examining knee injuries were the most highly cited and appear to be of high interest to current investigators. The prestige of an author's name appeared to be less influential to the number of citations. Clinical Relevance: The top 50 most cited articles list will provide researchers, medical students, residents, and fellows with a foundational list of the most important and influential academic contributions to the basketball literature.